Digitalizaton of Administration and Promotion System as Support System for the Bumdes Jati Unggul Business Unit - Anastesi Sayekti, Lulu; Sugiyanto; Norhikmah (Edumedia Solution, 2026)
In line with the times, village governments need to transform their services towards digital, including Badan Usaha Milik Desa (BUMDes). BUMDes are the economic driving force for local communities. In developing their business units, BUMDes require a good administration and promotion system. One BUMDes that has developed and been appreciated by the local community is BUMDes Binangun Jati Unggul, Jatirejo Village, Lendah Subdistrict, Kulon Progo Regency. This Community Service helps BUMDes Binangun Jati Unggul to solve the problems faced, namely the lack of digital publications and the unavailability of digital administration and personnel systems. The intended output of this activity is in the management aspect, namely improving the ability of BUMDes in managing digital administration and publications. The methods used are socialization and training. Training activities are carried out six times and mentoring is carried out for 3 months from October 13 to December 31, 2025. The results of the Community Service Program are in the form of increased understanding and skills of human resources in using the SIAK application and digital marketing. Community Service Activity runs well and smoothly. The targeted outputs in this activity have also been achieved: (1) in the management aspect, namely increasing the BUMDes' ability to manage digital administration and publications. The Administration and Personnel System (SIAK) and the addition of scanners have been made available to realize the digitalization of administration. With this system, the information technology assets owned by BUMDes have also increased. (2) In the marketing aspect, namely increasing the ability to manage digital publications in the form of creating attractive videos, photos, and posters regularly and continuously.